Integral sliding-mode controller for maximum power point tracking in the grid-connected photovoltaic systems - Nour-Eddine Tariba; Naima Ikken; Ahmed Haddou; Abdelhadi Bouknadel; Hafsa El Omari; Hamid El Omari (Institute of Advanced Engineering and Science, 2020)
The output power generated in the photovoltaic modules depends both on the solar radiation and the temperature of the solar cells. To maximize the efficiency of the system, it is required to monitor the maximum power point of the photovoltaic system. For this purpose, monitoring the maximum power point (MPPT) of photovoltaic systems should be as quick and accurately as possible for increasing energy production, which ultimately increases the cost-efficiency of the photovoltaic system. This paper proposes a new approach for MPPT) using the concept of the integral sliding mode controller (ISMC) to ensure fast and precise monitoring of the peak power. The performance of the ISMC is significantly influenced by the choice of the sliding surface. To assess the reliability ISMC control, the results have been compared with those of a PI controller. The results obtained are used to evaluate the performance of the ISMC strategy under different climatic conditions. Finally, the effectiveness of the proposed solution is confirmed using simulations in PSIM tools and experimental results were used to evaluate the effectiveness of the proposed approach.